Implementasi Prenatal Yoga dalam Kelas Ibu Hamil : Upaya Preventif Terhadap Ketidaknyamanan Fisik pada Ibu Hamil di Desa Tenaru - Putri Ancila Citra Prasetya (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Background: Anatomical readjustments during pregnancy commonly trigger musculoskeletal disorders and childbirth-related anxiety, impacting the overall well-being of the mother. In Desa Tenaru, physical discomfort is frequently normalized by pregnant women because they lack the necessary tools and techniques for effective pain management. Objective: This community service program aims to equip pregnant women with self-care skills through Prenatal Yoga to reduce physical discomfort and maintain emotional stability. Methods: The activity was conducted at the Balai Posyandu with 18 pregnant women as participants. The methods included an initial assessment using the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ), health education, demonstrations, and Prenatal Yoga practice, followed by a post-test evaluation. Results: Participant characteristics were dominated by the 20-35 age group (83%), primigravida (61%), and employed status (72%). Evaluation results showed a significant decrease in physical discomfort: before the intervention, the majority of participants experienced moderate discomfort (55.6%), which decreased to the low category (55.6%) after receiving education and practicing Prenatal Yoga. Conclusion: The implementation of Prenatal Yoga within the Pregnancy Class agenda is effective in reducing physical discomfort among pregnant women. This practice serves as a safe and holistic non-pharmacological solution to enhance maternal well-being and mental readiness for labor